Religious Unbelief in Three Western European Countries: Identifying and Characterizing Unbeliever Types Using Latent Class Analysis. Issue 3 (3rd July 2019) - Lindeman, Marjaana; van Elk, Michiel; Lipsanen, Jari; Marin, Pinja; Schjødt, Uffe
ABSTRACT: The different forms of religious unbelief are still much of an open question. Using data ( N = 4, 404) from three European countries—Finland, Denmark, and the Netherlands—we sought to identify underlying unbeliever groups among those with the strongest disbelief in God ( N = 2, 258). Latent class analyses were conducted on the nontheistic supernatural beliefs of this subsection of participants, resulting in the same three unbeliever groups in each country: analytic atheists, spiritual but not religious (SBNR), and uncertain nonbelievers. Next, we explored these groups on a variety of dimensions, especially on the group members' attitudes to religion, certainty of beliefs, cognitive dispositions, and worldview. One-way analyses of variance (ANOVAs) revealed similarities as well as distinct characters for each of the latent groups. The groups differed most in intuitive thinking style, overmentalizing bias, and other ontological confusions. To compare the latent groups to all other individuals who took part in the study, two discriminant analyses were run with all participants. This resulted in four meaningful dimensions that supported and extended the ANOVAs findings and allowed for the consideration of other (non)believers. Overall, this study supports earlier findings on analytic atheists and SBNR while providing new information about their dispositions. Of interest, the uncertain nonbeliever group has been largely unexplored previously, and it should gain more attention in future studies.